A precipitation hardenable nickel-based alloy welding wire and a method of making the same

CN120438895BActive Publication Date: 2026-10-30WUXI WEISHI POWER TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510923280.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2026-10-30
Estimated Expiration
2045-07-04

AI Technical Summary

Technical Problem

[0007]本发明旨在提供一种沉淀硬化型镍基合金焊丝及其制备方法,通过成分优化和工艺创新,解决现有技术中高温强度不足、抗热裂性差和低温韧性低等问题,满足高端装备制造领域对高性能焊接材料的需求

Benefits of technology

(1)本技术通过引入钇(0.01-0.05%)与钨(0.5-2%)的复合微合金化设计,构建了“晶界强化-固溶强化-沉淀强化”的三重作用机制,钇作为稀土元素,通过形成Y2O3纳米颗粒(粒径<20nm)钉扎晶界,使焊接热影响区裂纹率从传统工艺的18.5%降至3.5%-4.8%,同时抑制晶粒粗化,晶粒度细化至25-35μm,钨元素通过固溶强化提升基体点阵畸变能,使700℃抗拉强度突破1000MPa(最高达1080MPa),较现有ERNiCrMo-3焊丝提升36%-44%,此外,精准控制铌钽比(2-3:1)与铝钛比(1-1.5:1),促使MC型碳化物与γ'相均匀析出,γ'相尺寸细化至55-70nm,实现强度(σb≥950MPa)与塑性(δ≥18%)的平衡,解决了传统镍基合金“强而不韧”或“韧而不强”的难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120438895B_ABST
    Figure CN120438895B_ABST
Patent Text Reader

Abstract

The application belongs to the field of nickel-based alloy materials, and discloses a precipitation hardening type nickel-based alloy welding wire and a preparation method thereof, which comprises the following components in percentage by mass: nickel 50%-60%, chromium 15%-20%, iron 15%-20%, molybdenum 2%-4%, niobium 2%-5%, tantalum 0.01%-2%, aluminum 0.2%-2%, titanium 0.5%-1.2%, carbon 0.03%-0.08%, manganese 0.1%-0.5%, silicon 0.1%-0.5%, magnesium 0.01%-0.05%, yttrium 0.01%-0.05%, tungsten 0.5%-2%, cobalt 0.1%-0.6%, boron 0.001%-0.02%, and the balance is impurities; the application aims to provide a precipitation hardening type nickel-based alloy welding wire and a preparation method thereof, and through component optimization and process innovation, a nickel-based alloy welding wire with high-temperature strength, excellent heat crack resistance and welding toughness is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nickel-based alloy materials technology, specifically to a precipitation-hardening nickel-based alloy welding wire and its preparation method. Background Technology

[0002] Welding wire is a metal wire used as filler metal or as a conductive electrode in welding. In gas welding and tungsten inert gas welding, welding wire is used as filler metal; in submerged arc welding, electroslag welding and other gas metal arc welding, welding wire is both filler metal and conductive electrode.

[0003] Nickel-based alloys are a class of alloys that possess high strength and certain resistance to oxidation and corrosion at high temperatures of 650–1000℃. Based on their main properties, they are further subdivided into nickel-based heat-resistant alloys, nickel-based corrosion-resistant alloys, nickel-based wear-resistant alloys, nickel-based precision alloys, and nickel-based shape memory alloys.

[0004] Nickel-based alloy welding wire has excellent resistance to reactive gases, harsh media, and reducing acid media corrosion. It also features high strength, good plasticity, cold and hot deformation and processing, and weldability.

[0005] Existing methods for preparing nickel-based alloy welding wire typically involve melting raw materials in a vacuum induction furnace, casting them into steel ingots, and then performing hot forging, hot rolling annealing, pickling, grinding, first drawing, hydrogen annealing, second drawing, and winding to obtain the nickel-based alloy welding wire. However, this method is prone to hot cracking during welding, which reduces the service life of the nickel-based alloy welding wire and fails to meet people's needs.

[0006] Therefore, in order to solve the above problems, the present invention provides a precipitation-hardening nickel-based alloy welding wire and its preparation method, providing a nickel-based alloy welding wire with high-temperature strength, excellent resistance to hot cracking and welding toughness. Summary of the Invention

[0007] This invention aims to provide a precipitation-hardening nickel-based alloy welding wire and its preparation method. Through composition optimization and process innovation, it solves the problems of insufficient high-temperature strength, poor thermal crack resistance and low-temperature toughness in the existing technology, and meets the demand for high-performance welding materials in the field of high-end equipment manufacturing.

[0008] To achieve the above objectives, the present invention provides the following technical solution: The technical solution provided by this invention is: a precipitation-hardening nickel-based alloy welding wire, comprising the following components by mass percentage: nickel 50%-60%, chromium 15%-20%, iron 15%-20%, molybdenum 2%-4%, niobium 2%-5%, tantalum 0.01%-2%, aluminum 0.2%-2%, titanium 0.5%-1.2%, carbon 0.03%-0.08%, manganese 0.1%-0.5%, silicon 0.1%-0.5%, magnesium 0.01%-0.05%, yttrium 0.01%-0.05%, tungsten 0.5%-2%, cobalt 0.1%-0.6%, boron 0.001%-0.02%, with the balance being impurities.

[0009] Furthermore, the mass ratio of niobium to tantalum is (2-3):1.

[0010] Furthermore, the mass ratio of aluminum to titanium is (1-1.5):1.

[0011] Furthermore, the mass percentage of carbon is 0.04%-0.07%.

[0012] Furthermore, the mass ratio of yttrium to tungsten is (0.05-0.1):1.

[0013] A method for preparing a precipitation-hardening nickel-based alloy welding wire includes the following steps: S1: Mix the raw materials according to the specified proportions and melt them in a vacuum induction melting furnace at a temperature of 1500-1600℃, maintaining a vacuum level of 1×10⁻⁶. -2 Pa, melting time is 60-90 minutes and electromagnetic stirring is applied to obtain alloy melt; S2: The alloy melt is made into an electrode rod and cast using an electroslag remelting process. Specifically, a mixed slag of CaF2-Al2O3-SiO2 (mass ratio 7:2:1) is used as the slag system, the slag pool depth is 50-100mm, the welding current is controlled at 5000-8000A, the welding voltage is 30-50V, the remelting speed is 0.5-1.5kg / min, and water is circulated in the crystallizer for cooling at a rate of 10-30℃ / s to obtain an alloy ingot. S3: Heat the alloy ingot to 1100-1200℃, hold for 4-6 hours, and then cool it to room temperature in the furnace to obtain a homogenized alloy ingot. S4: Heat the homogenized alloy ingot to 950-1050℃ and hot roll or hot forge it, with a deformation of 30%-50%, to obtain the alloy billet. S5: The alloy billet is cold-drawn at a speed of 0.5-1.5 m / min, with a deformation of 10%-20% per drawing. During the drawing process, 2-4 intermediate annealings are performed at a temperature of 700-800℃ for 1-2 hours. After each annealing, the material is water-cooled to room temperature to obtain precipitation-hardening nickel-based alloy welding wire.

[0014] Furthermore, following S5, there is also a surface treatment step S6, which is as follows: S6.1: Immerse the welding wire in a passivation solution (pH=3-5, temperature 40-60℃) containing nano-alumina particles (particle size 20-50nm) for 5-10 minutes; S6.2: After removal, bake at 300-400℃ for 1-2 hours to form an oxide film with a thickness of 2-5μm.

[0015] The beneficial effects of this technical solution are: (1) This technology introduces a composite microalloying design of yttrium (0.01-0.05%) and tungsten (0.5-2%) to construct a triple action mechanism of "grain boundary strengthening - solid solution strengthening - precipitation strengthening". As a rare earth element, yttrium forms Y2O3 nanoparticles (particle size <20nm) to pin the grain boundaries, reducing the crack rate in the weld heat-affected zone from 18.5% in the traditional process to 3.5%-4.8%, while inhibiting grain coarsening and refining the grain size to 25-35μm. Tungsten enhances the matrix lattice distortion through solid solution strengthening. It can achieve a tensile strength of over 1000MPa (up to 1080MPa) at 700℃, which is 36%-44% higher than the existing ERNiCrMo-3 welding wire. In addition, by precisely controlling the niobium-tantalum ratio (2-3:1) and aluminum-titanium ratio (1-1.5:1), it promotes the uniform precipitation of MC-type carbides and γ' phase, and refines the γ' phase size to 55-70nm, achieving a balance between strength (σb≥950MPa) and plasticity (δ≥18%), thus solving the problem of traditional nickel-based alloys being "strong but not tough" or "tough but not strong".

[0016] (2) The preparation process adopts the synergistic technology of "electroslag remelting + gradient annealing + nano passivation" to achieve full-process microstructure control from melting to surface treatment. Electromagnetic stirring (frequency 40-70Hz) is applied during vacuum induction melting, combined with high temperature of 1500-1600℃ and 1×10 -2 High vacuum (Pa) ensures uniform dissolution of refractory elements (such as tungsten and tantalum), with a compositional uniformity error of <1.5%. During the electroslag remelting stage, the cooling rate is controlled at 10-30℃ / s to suppress columnar crystal growth, achieving an equiaxed crystal ratio >95% and a macroscopic segregation of <0.8%. During cold drawing, 2-4 intermediate annealing processes (700-800℃) with water cooling are employed to control the γ' phase precipitation kinetics, optimizing the dislocation density to 102. 15To avoid excessive work hardening, the wire is ultimately passivated with nano-alumina (particle size 20-50nm) to form a 2-5μm anti-oxidation film on the surface of the welding wire, improving corrosion resistance by more than 50%.

[0017] (3) This technical solution achieves a leapfrog improvement in the comprehensive performance of nickel-based alloy welding wire through dual innovation in composition and process: the creep life at 700℃ reaches 520-630h (an increase of 30%-40%), the impact energy at -196℃ reaches 155-175J (an increase of 50%-75%), the welding crack rate is reduced by 67%-78%, and the production efficiency is increased by 20%-30%. The six embodiments cover high-end equipment (such as aero-engines and nuclear power pipelines), special environments (such as cryogenic LNG storage tanks and ultra-high temperature turbine blades), and precision manufacturing (such as electron beam welding). It solves the performance bottlenecks of traditional welding wire in terms of high temperature strength, crack resistance, and low temperature toughness. At the same time, the gradient hot processing and low temperature melting processes reduce energy consumption by 10%-18%, which is in line with the trend of green manufacturing. Attached Figure Description

[0018] Figure 1 This is a data table for Example 1 of the precipitation-hardening nickel-based alloy welding wire and its preparation method proposed in this invention; Figure 2 This is a data table for Example 2 of the precipitation-hardening nickel-based alloy welding wire and its preparation method proposed in this invention; Figure 3 This is a data table for Example 3 of the precipitation-hardening nickel-based alloy welding wire and its preparation method proposed in this invention; Figure 4 This is a data table for Example 4 of the precipitation-hardening nickel-based alloy welding wire and its preparation method proposed in this invention; Figure 5 This is a data table for Example 5 of the precipitation-hardening nickel-based alloy welding wire and its preparation method proposed in this invention; Figure 6 This is a data table for Example 6 of the precipitation-hardening nickel-based alloy welding wire and its preparation method proposed in this invention; Figure 7 This is a comparative table of data for various embodiments of the precipitation-hardening nickel-based alloy welding wire and its preparation method proposed in this invention; Figure 8 This is a comparison table of the differences between various embodiments of the precipitation-hardening nickel-based alloy welding wire and its preparation method proposed in this invention. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. The specific implementation process is as follows: Example 1: Please see Figure 1-7 The present invention provides a technical solution: a method for preparing precipitation-hardening nickel-based alloy welding wire, comprising the following components by mass percentage: nickel 60%, chromium 15%, iron 15%, molybdenum 2%, niobium 2%, tantalum 1% (niobium-tantalum ratio 2:1), aluminum 1.5%, titanium 1% (aluminum-titanium ratio 1.5:1), carbon 0.08%, manganese 0.5%, silicon 0.3%, magnesium 0.05%, yttrium 0.02%, tungsten 1%, cobalt 0.5%, boron 0.01%, with the balance being impurities; The preparation steps are as follows: S1: Melting: Preheat a 50kg vacuum induction furnace to 800℃, then raise the temperature to 1550℃, with a vacuum degree of 1×10⁻⁶. -2 Pa, electromagnetic stirring frequency 50Hz, melting for 75 minutes; S2: Electroslag remelting, electrode rod diameter φ50mm, slag system CaF2-Al2O3-SiO2 (7:2:1), slag pool depth 80mm, current 6500A, voltage 40V, remelting speed 1.2kg / min, crystallizer water cooling rate 25℃ / s; S3: Homogenization: Hold at 1150℃ for 5 hours, then cool with the furnace; S4: Hot rolling: Heated to 1000℃, hot rolling in 3 passes, total deformation 40%, final rolling temperature 880℃, to obtain φ20mm billet; S5: Cold drawing: 4 drawing steps, each with a deformation of 15%, drawing speed of 1m / min; annealing at 750℃ for 3 times, each time for 1.5 hours, followed by water cooling; S6: Passivation: passivation solution pH=4, temperature 50℃, soak for 10 minutes, bake at 350℃ for 1.5 hours; The 60% nickel content provides good matrix toughness, while 15% chromium and 2% molybdenum form a basic antioxidant and corrosion resistant system. The 2:1 niobium-tantalum ratio promotes the uniform dispersion and precipitation of MC-type carbides (NbC, TaC), enhancing the intragranular strengthening effect. The 1.5:1 aluminum-titanium ratio ensures the uniform distribution of the γ' phase (Ni3(Al,Ti)) and refines its size to 65nm, improving high-temperature strength. 0.02% yttrium forms Y2O3 nanoparticles that pin grain boundaries and inhibit grain growth. 1% tungsten solid solution strengthens the matrix, resulting in a tensile strength of 980MPa at 700℃ and a creep rupture life of 583h, which is more than 30% better than existing technologies. Vacuum induction melting at a high temperature of 1550℃ and 1×10 -2 A vacuum level of 100 MPa ensures the complete dissolution of refractory elements, while electromagnetic stirring maintains a compositional uniformity error of <1.5%. The electroslag remelting stage employs a cooling rate of 25℃ / s and a slag pool depth of 80mm, combined with a CaF2-Al2O3-SiO2 slag system, effectively removing impurities and yielding a dense alloy ingot. Three intermediate annealing processes at 750℃, combined with water cooling, precisely control the precipitation of the γ' phase, achieving a balance between strength (σb=1020MPa) and plasticity (δ=22%). Surface nano-alumina passivation treatment forms a 2-5μm oxide film, improving corrosion resistance by over 50%. The impact energy at -196℃ has been increased to 62J, the welding crack rate has been reduced to 4.2%, and the grain size has been refined to 30μm. Its comprehensive performance is suitable for medium-load high-temperature scenarios such as the combustion chamber of aero-engines.

[0020] Example 2: Please see Figure 1-7 The present invention provides a technical solution: a method for preparing precipitation-hardening nickel-based alloy welding wire, comprising the following components by mass percentage: nickel 53%, chromium 17%, iron 15%, molybdenum 3%, niobium 4%, tantalum 2% (niobium-tantalum ratio 2:1), aluminum 1.8%, titanium 1.2% (aluminum-titanium ratio 1.5:1), carbon 0.06%, manganese 0.4%, silicon 0.3%, magnesium 0.05%, yttrium 0.03%, tungsten 1.5%, cobalt 0.6%, boron 0.02%, with the balance being impurities; The preparation steps are as follows: S1: Melting: Temperature 1580℃, Vacuum 1×10⁻⁶ -2 Pa, electromagnetic stirring at 60 Hz, melting for 80 minutes; S2: Electroslag remelting: slag pool depth 90mm, current 7000A, voltage 45V, remelting speed 1.3kg / min, cooling rate 30℃ / s; S3: Homogenization: Hold at 1180℃ for 4.5 hours; S4: Hot rolling: Hot rolling at 1020℃, deformation amount 45%, final rolling temperature 890℃, to obtain φ22mm billet; S5: Cold drawing: 5 drawing steps, 18% deformation each time, speed 1.2m / min; 4 annealing steps at 780℃, 1 hour each time, water cooling; S6: Passivation: passivation solution pH=3.5, temperature 55℃, soak for 8 minutes, bake at 380℃ for 1 hour; The molybdenum content is increased to 3% and the tungsten content to 1.5%, which enhances the solid solution effect and precipitation hardening effect. The chromium content of 17% enhances the antioxidant capacity. The precise control of the niobium-tantalum ratio of 2:1 and the aluminum-titanium ratio of 1.5:1 enables the uniform precipitation and refinement of MC-type carbides and γ' phases, with the γ' phase size reaching 60nm. The yttrium content of 0.03% further optimizes the grain boundary stability, reduces the segregation of impurities at the grain boundaries, and reduces crack sensitivity. High-temperature melting at 1580℃ and electromagnetic stirring at 60Hz promote the full dissolution and uniform mixing of alloying elements; rapid cooling at 30℃ / s and a slag pool depth of 90mm during the electroslag remelting stage, combined with a welding current of 7000A and a voltage of 45V, effectively removes gases and inclusions, resulting in a dense and homogeneous alloy ingot; four intermediate annealings at 780℃, each with 1-hour water cooling, optimize the dislocation density to 10. 15 On the order of / m², it improves the work hardening effect while avoiding embrittlement; The tensile strength at 700℃ reaches 1050MPa, the highest value in the examples; the service life reaches 612h; the impact energy at -196℃ is 59J; the welding crack rate is as low as 3.8%; and the grain size is refined to 28μm. This solution is suitable for harsh environments such as nuclear power high-pressure pipelines and can withstand long-term high-temperature and high-pressure media erosion, improving the reliability of welded joints by more than 50%.

[0021] Example 3: Please see Figure 1-7 The present invention provides a technical solution: a method for preparing precipitation-hardening nickel-based alloy welding wire, comprising the following components by mass percentage: nickel 57%, chromium 19%, iron 15%, molybdenum 2%, niobium 2.5%, tantalum 1% (niobium-tantalum ratio 2.5:1), aluminum 1.2%, titanium 0.8% (aluminum-titanium ratio 1.5:1), carbon 0.04%, manganese 0.2%, silicon 0.4%, magnesium 0.02%, yttrium 0.01%, tungsten 0.5%, cobalt 0.1%, boron 0.001%, with the balance being impurities; The preparation steps are as follows: S1: Melting: Temperature 1520℃, Vacuum 1×10⁻⁶ -2 Pa, electromagnetic stirring at 40 Hz, melting for 65 minutes; S2: Electroslag remelting: Argon protection, slag pool depth 50mm, current 5000A, voltage 30V, remelting speed 0.5kg / min, cooling rate 10℃ / s; S3: Homogenization: Hold at 1120℃ for 5.5 hours; S4: Hot rolling: 980℃ hot rolling, deformation amount 35%, final rolling temperature 860℃, to obtain φ18mm billet; S5: Cold drawing: drawn in 3 stages, each stage with a deformation of 12%, at a speed of 0.8 m / min; annealed twice at 720℃ for 2 hours each time, then water-cooled; S6: Passivation: passivation solution pH=4.5, temperature 45℃, soak for 5 minutes, bake at 320℃ for 2 hours; Chromium (19%) enhances oxidation resistance, while molybdenum (2%) maintains a certain solid solution strengthening effect. A niobium-tantalum ratio of 2.5:1 ensures that MC-type carbides are distributed in isolated granular form, avoiding brittleness caused by continuous precipitation at grain boundaries. An aluminum-titanium ratio of 1.5:1 guarantees effective precipitation strengthening of the γ' phase. Yttrium (0.01%) and tungsten (0.5%) can still play a grain boundary strengthening role, forming fine Y2O3 particles and solid solution strengthening effect, reducing the sensitivity to welding cracks. The low-temperature melting at 1520℃ and electromagnetic stirring at 40Hz ensure the dissolution of alloying elements while reducing energy consumption; the electroslag remelting under argon protection, combined with a slag pool depth of 50mm, a current of 5000A and a voltage of 30V, and a cooling rate of 10℃ / s, effectively reduces oxidation and obtains alloy ingots with uniform microstructure; the two intermediate annealings at 720℃, each with 2 hours of water cooling, simplify the process flow and control the precipitation of γ' phase to ensure certain strength and plasticity; The welding crack rate is 4.5%, which is 70% lower than that of yttrium-free tungsten alloys; the elongation reaches 21%; and the grain size is 32μm, proving that the inert gas protection has a limited impact on process stability. This solution is suitable for industrial mass production and can be used for routine welding of chemical containers. In a corrosive environment at 650℃, its service life is extended by 2 years compared to traditional welding wires, and its overall cost performance is outstanding.

[0022] Example 4: Please see Figure 1-7 The present invention provides a technical solution: a method for preparing precipitation-hardening nickel-based alloy welding wire, comprising the following components by mass percentage: nickel 50%, chromium 20%, iron 15%, molybdenum 4%, niobium 2.5%, tantalum 1% (niobium-tantalum ratio 2.5:1), aluminum 2%, titanium 1.2% (aluminum-titanium ratio 1.67:1), carbon 0.08%, manganese 0.5%, silicon 0.5%, magnesium 0.05%, yttrium 0.05%, tungsten 2%, cobalt 0.4%, boron 0.01%, with the balance being impurities; The preparation steps are as follows: S1: Melting: Temperature 1600℃, Vacuum 1×10⁻⁶ -2 Pa, electromagnetic stirring at 70 Hz, melting for 90 minutes; S2: Electroslag remelting: slag pool depth 100mm, current 8000A, voltage 50V, remelting speed 1.5kg / min, cooling rate 30℃ / s; S3: Homogenization: Hold at 1200℃ for 4 hours; S4: Hot rolling: Hot rolling at 1050℃, deformation amount 50%, final rolling temperature 900℃, to obtain φ16mm billet; S5: Cold drawing: 6 drawing steps, 15% deformation each time, speed 1.5m / min; annealing at 800℃ 4 times, 1 hour each time, water cooling; S6: Passivation: Passivation solution pH=3, temperature 60℃, soak for 7 minutes, bake at 400℃ for 1 hour; The high alloying design with 20% chromium, 4% molybdenum, and 2% tungsten forms a strong anti-oxidation layer (Cr2O3) and a high density of solid solution atoms (W), significantly improving high-temperature oxidation resistance and strength performance; the 2.5:1 niobium-tantalum ratio promotes the dispersed distribution of MC-type carbides and enhances intragranular strengthening; 0.05% yttrium significantly inhibits grain boundary oxidation, refines grains, and improves grain boundary stability. High-temperature melting at 1600℃ and electromagnetic stirring at 70Hz ensure that high-melting-point elements (such as W) are fully dissolved and uniformly distributed, with a composition uniformity error of <1.5%; rapid cooling at 30℃ / s and a slag pool depth of 100mm during the electroslag remelting stage, combined with 8000A current and 50V voltage, yields an alloy ingot with a dense structure and fine grains; 50% hot deformation and four intermediate annealings at 800℃ break up coarse carbides, refining the γ' phase size to 55nm, further enhancing the alloy properties; The fatigue life reaches 630 hours at 700℃, exceeding international standards by 40%; the impact energy at -196℃ is 64J, setting a new record; the welding crack rate is as low as 3.5%; the grain size is refined to 25μm; this solution breaks through the high-temperature limit of traditional nickel-based alloys, is suitable for ultra-high temperature scenarios such as turbine blades in aerospace engines, can withstand high temperatures of 900℃ and cyclic loads, and has a fatigue life of 10 hours. 7 More than once.

[0023] Example 5: Please see Figure 1-7 The present invention provides a technical solution: a method for preparing precipitation-hardening nickel-based alloy welding wire, comprising the following components by mass percentage: nickel 60%, chromium 15%, iron 15%, molybdenum 2%, niobium 3%, tantalum 2% (niobium-tantalum ratio 1.5:1), aluminum 0.8%, titanium 0.8% (aluminum-titanium ratio 1:1), carbon 0.03%, manganese 0.1%, silicon 0.1%, magnesium 0.01%, yttrium 0.01%, tungsten 0.5%, cobalt 0.6%, boron 0.02%, with the balance being impurities; The preparation steps are as follows: S1: Melting: Temperature 1500℃, Vacuum 1×10 -2 Pa, electromagnetic stirring at 45 Hz, melting for 60 minutes; S2: Electroslag remelting: slag pool depth 60mm, current 5000A, voltage 35V, remelting speed 0.8kg / min, cooling speed 15℃ / s; S3: Homogenization: Hold at 1100℃ for 6 hours; S4: Hot rolling: 950℃ hot rolling, deformation amount 30%, final rolling temperature 850℃, to obtain φ24mm billet; S5: Cold drawing: drawn in 4 stages, with a deformation of 12% each time, at a speed of 0.6 m / min; annealed at 730℃ for 3 times, 1.5 hours each time, and water-cooled; S6: Passivation: passivation solution pH=5, temperature 40℃, soak for 10 minutes, bake at 330℃ for 1.5 hours; The low-chromium design with 60% nickel and 15% chromium can still achieve a high-temperature strength of 950 MPa through the combination of yttrium (0.01%) and tungsten (0.5%), proving the synergistic effect of matrix toughness and reinforcing phase; When the aluminum-titanium ratio is 1:1, the γ' phase size is 75 nm. Although the strength is slightly reduced, the plasticity is well maintained. The high nickel content of 60% enhances the toughness of the matrix, while 15% chromium and 2% molybdenum provide basic corrosion resistance. Although the niobium-tantalum ratio of 1.5:1 and the aluminum-titanium ratio of 1:1 deviate from the optimal ratio, they can still form certain carbides and γ' phase reinforcement. The combination of 0.01% yttrium and 0.5% tungsten achieves a high-temperature strength of 950 MPa, proving the synergistic effect of matrix toughness and reinforcing phase. The aluminum-titanium ratio of 1:1 coarsens the γ' phase to 75 nm. Although the strength is slightly reduced, the aluminum-rich γ' phase (Ni3Al) enhances the resistance to liquid metal corrosion. Low-temperature melting at 1500℃ and electromagnetic stirring at 45Hz shorten the melting time to 60 minutes and reduce energy consumption by 10%; a cooling rate of 15℃ / s and a slag pool depth of 60mm during the electroslag remelting stage, combined with a current of 5000A and a voltage of 35V, yields alloy ingots with uniform microstructure; a 30% hot deformation amount and three intermediate annealing processes at 730℃ simplify the processing flow and increase production efficiency by 20%, verifying the practicality of the lower limit of deformation amount in the claims. The impact energy reaches 60J at -196℃, meeting the welding requirements of the cryogenic zone of LNG storage tanks; the energy consumption is reduced by 18% in terms of process, and the surface roughness of the welding wire Ra<1.6μm, which can be directly used in automatic welding equipment; this solution achieves green manufacturing while ensuring low-temperature toughness, and the overall cost is reduced by 12% compared with the traditional solution, making it suitable for the field of liquefied natural gas storage and transportation.

[0024] Example 6: Please see Figure 1-7The present invention provides a technical solution: a method for preparing precipitation-hardening nickel-based alloy welding wire, comprising the following components by mass percentage: nickel 53%, chromium 18%, iron 15%, molybdenum 3%, niobium 3.5%, tantalum 1.8% (niobium-tantalum ratio 1.94:1), aluminum 1.6%, titanium 1.1% (aluminum-titanium ratio 1.45:1), carbon 0.065%, manganese 0.35%, silicon 0.25%, magnesium 0.035%, yttrium 0.04%, tungsten 1.7%, cobalt 0.3%, boron 0.015%, with the balance being impurities; The preparation steps are as follows: S1: Melting: Temperature 1560℃, Vacuum 1×10⁻⁶ -2 Pa, electromagnetic stirring 55Hz, melting for 70 minutes; S2: Electroslag remelting: slag pool depth 70mm, current 6500A, voltage 42V, remelting speed 1.1kg / min, cooling rate 22℃ / s; S3: Homogenization: Hold at 1170℃ for 4.8 hours; S4: Hot rolling: Hot rolling at 1010℃, deformation amount 42%, final rolling temperature 870℃, to obtain φ20mm billet; S5: Cold drawing: 5 drawing steps, 16% deformation each time, speed 1.1m / min; annealing at 760℃ 3 times, 1.2 hours each time, water cooling; S6: Passivation: passivation solution pH=3.8, temperature 52℃, soak for 8 minutes, bake at 360℃ for 1.3 hours; The niobium-tantalum ratio of 1.94:1 and the aluminum-titanium ratio of 1.45:1 are close to the ideal ratios (2:1 and 1.5:1), which promotes the uniform precipitation of MC-type carbides and γ' phase. The γ' phase size is refined to 62nm, providing a stable and efficient precipitation strengthening effect for the alloy. This results in a tensile strength of 1030MPa at 700℃ and a creep rupture life of 595h, achieving a balanced improvement in strength and creep performance. The combined addition of 0.04% yttrium and 1.7% tungsten allows yttrium to form Y2O3 nanoparticles that pin grain boundaries, while tungsten enhances the solid solution effect. The synergistic effect of the two inhibits the continuous precipitation of grain boundary carbides, reducing the welding crack rate to 4.0%, while improving the high-temperature stability and crack resistance of the alloy. A homogenization temperature of 1170℃ combined with 4.8 hours of heat treatment precisely matched the diffusion coefficient of alloying elements, reducing the segregation of the alloy to 0.8% (compared to ≥1.5% in conventional processes), significantly improving compositional uniformity and laying the foundation for subsequent processing and performance stability. In the cold drawing stage, the combination of a drawing speed of 1.1 m / min and annealing for 1.2 hours effectively balanced production efficiency and microstructure control. Through three intermediate annealing processes and appropriate deformation amounts, the precipitation kinetics of the γ' phase were controlled, avoiding excessive work hardening. This method is suitable for preparing Φ2-4mm fine wires, meeting the requirements of precision welding wire specifications and performance.

[0025] Please see Figure 7 Key difference analysis: High strength and creep resistance: The tensile strength at 700℃ in all embodiments exceeds 950MPa, with Embodiment 4 reaching 1080MPa, representing a 36%-44% improvement over existing ERNiCrMo-3 welding wires; the creep rupture life at 700℃ is 520-630h, an improvement of 30%-40%. This is attributed to the triple mechanism of "grain boundary strengthening - solid solution strengthening - precipitation strengthening" formed by yttrium-tungsten composite microalloying in the composition, as well as the precisely controlled niobium-tantalum ratio and aluminum-titanium ratio, which promote the uniform dispersion and precipitation of MC-type carbides and γ' phase.

[0026] Improved low-temperature toughness: The impact energy at -196℃ is 58-64J, while traditional technologies typically have less than 50J. For example, Example 4 achieves an impact energy of 64J. By optimizing the alloy composition and process, refining the grains, and achieving a uniform microstructure, the toughness performance under low-temperature conditions is effectively improved, meeting the requirements of cryogenic applications such as LNG storage tanks.

[0027] The welding crack rate was 3.5%-5.0%, significantly lower than the 18.5% of the traditional process. Taking 3.5% in Example 4 and 3.8% in Example 2 as examples, yttrium-formed Y2O3 nanoparticles pinned grain boundaries, inhibiting grain coarsening and crack propagation. At the same time, the electroslag remelting process effectively removed impurities and controlled the cooling rate, resulting in a dense and uniform microstructure, which greatly reduced the crack sensitivity of the weld heat-affected zone.

[0028] The grain size is 25-35μm, which is finer than that of traditional processes. In Example 4, the grain size reached 25μm. Through processes such as high-temperature melting, electromagnetic stirring, and rapid cooling, grain growth was effectively suppressed, and the overall performance of the material was improved.

[0029] The γ' phase size is refined to 55-70 nm, which is a significant improvement over the >100 nm of the traditional technology. For example, 55 nm in Example 4 and 60 nm in Example 2. Precise control of the component ratio promotes the uniform and fine precipitation of the γ' phase, achieving a good balance between strength and plasticity.

[0030] The macroscopic segregation was all <0.8% (0.8% in Example 6). The electromagnetic stirring and electroslag remelting process in vacuum induction melting ensured the high uniformity of the alloy composition, improved the impurity removal rate by 40%, and the equiaxed crystal ratio was >95%, which is higher than about 70% of the traditional casting process.

[0031] Example 5 achieves an 18% reduction in energy consumption and a 20% increase in production efficiency. Processes such as low-temperature melting (starting from 1500℃) and gradient heat treatment ensure performance while conforming to the trend of green manufacturing and reducing production costs.

[0032] Each embodiment, through nano-alumina passivation treatment, improves corrosion resistance by more than 50% and forms a 2-5μm anti-oxidation film on the surface, effectively enhancing the service life of the material in corrosive environments.

[0033] This technology, through the synergistic effect of composition design and process innovation, comprehensively surpasses existing technologies in terms of mechanical properties, crack resistance, microstructure, and process characteristics. It solves the problems of insufficient high-temperature strength, poor thermal crack resistance, and low-temperature toughness of traditional nickel-based alloy welding wires, providing high-performance, low-cost, and environmentally friendly welding material solutions for high-end equipment manufacturing fields such as aerospace, nuclear power, and cryogenics.

[0034] The above descriptions are merely embodiments of the present invention. Commonly known technical solutions or characteristics in the solutions are not described in detail here. It should be noted that those skilled in the art can make several modifications and improvements without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application shall be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. A precipitation-hardening nickel-based alloy welding wire, characterized in that, By weight percentage, it includes the following components: Nickel 50%-60%, Chromium 15%-20%, Iron 15%-20%, Molybdenum 2%-4%, Niobium 2%-5%, Tantalum 0.01%-2%, Aluminum 0.2%-2%, Titanium 0.5%-1.2%, Carbon 0.03%-0.08%, Manganese 0.1%-0.5%, Silicon 0.1%-0.5%, Magnesium 0.01%-0.05%, Yttrium 0.01%-0.05%, Tungsten 0.5%-2%, Cobalt 0.1%-0.6%, Boron 0.001%-0.02%, with the balance being impurities.

2. The precipitation-hardening nickel-based alloy welding wire according to claim 1, characterized in that: The mass ratio of niobium to tantalum is (2-3):

1.

3. The precipitation-hardening nickel-based alloy welding wire according to claim 2, characterized in that: The mass ratio of aluminum to titanium is (1-1.5):

1.

4. The precipitation-hardening nickel-based alloy welding wire according to claim 3, characterized in that: The mass percentage of carbon is 0.04%-0.07%.

5. The precipitation-hardening nickel-based alloy welding wire according to claim 1, characterized in that: The mass ratio of yttrium to tungsten is (0.05-0.1):

1.

6. A method for preparing a precipitation-hardening nickel-based alloy welding wire as described in any one of claims 1-5, characterized in that, Includes the following steps: S1: Mix the raw materials according to the specified proportions and melt them in a vacuum induction melting furnace at a temperature of 1500-1600℃, maintaining a vacuum level of 1×10⁻⁶. -2 Pa, melting time is 60-90 minutes and electromagnetic stirring is applied to obtain alloy melt; S2: The alloy melt is made into an electrode rod and cast using an electroslag remelting process. Specifically, a CaF2-Al2O3-SiO2 mixed slag with a mass ratio of 7:2:1 is used as the slag system. The slag pool depth is 50-100mm, the welding current is controlled at 5000-8000A, the welding voltage is 30-50V, the remelting speed is 0.5-1.5kg / min, and water cooling is carried out in the crystallizer at a cooling rate of 10-30℃ / s to obtain an alloy ingot. S3: Heat the alloy ingot to 1100-1200℃, hold for 4-6 hours, and then cool it to room temperature in the furnace to obtain a homogenized alloy ingot. S4: Heat the homogenized alloy ingot to 950-1050℃ and hot roll or hot forge it, with a deformation of 30%-50%, to obtain the alloy billet. S5: The alloy billet is cold-drawn at a speed of 0.5-1.5 m / min, with a deformation of 10%-20% per drawing. During the drawing process, 2-4 intermediate annealings are performed at a temperature of 700-800℃ for 1-2 hours. After each annealing, the billet is water-cooled to room temperature to obtain the precipitation-hardening nickel-based alloy welding wire.

7. The preparation method according to claim 6, characterized in that: The step S5 is followed by a surface treatment step S6, which specifically includes: S6.1: Immerse the welding wire in a passivation solution containing nano-alumina particles for 5-10 minutes. The nano-alumina particles have a particle size of 20-50 nm. The passivation solution has a pH of 3-5 and a temperature of 40-60°C. S6.2: After removal, bake at 300-400℃ for 1-2 hours to form an oxide film with a thickness of 2-5μm.

Citation Information

Patent Citations

  • Precipitation strengthened nickel based welding material for fusion welding of superalloys

    CN105163898A

  • Nickel base alloy welding wire for high-temperature alloy fusion welding and preparation method and application thereof

    CN111318835A